2014
DOI: 10.1292/jvms.14-0374
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Type 1 Infection in Two Pet Marmosets in Japan

Abstract: An 8-month-old common marmoset (Callithrix jacchus) was presented with tic-like symptoms, and a 2-year-old pigmy marmoset (Callithrix pygmaea) was presented with dyspnea and hypersalivation. Both monkeys died within a few days, and necropsies were performed. Histopathological examinations revealed ulcerative stomatitis with epithelial cell swelling and eosinophilic intranuclear inclusion bodies in the oral epithelium of both cases. In the central and peripheral nervous systems, neuronal cell degeneration with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…This profile has also been reported in other studies related to HSV-1, in P. pithecia and in C. jacchus [36,39]. The histopathological findings that we visualize in the brains of the animals corroborate with those of other reports regarding the presence of gliosis, neuroniophagia, eosinophilic inclusion corpuscle, monolymphocytic meningitis and dilated and congested blood vessels [4,11,16,17,20,21,[35][36][37][38][39]42]. We observed that the kidneys of the monkeys presented areas of necrosis, marked tubulonefrosis and ballooning degeneration with hyaline material, interstitial hemorrhage with increased Bowman space.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This profile has also been reported in other studies related to HSV-1, in P. pithecia and in C. jacchus [36,39]. The histopathological findings that we visualize in the brains of the animals corroborate with those of other reports regarding the presence of gliosis, neuroniophagia, eosinophilic inclusion corpuscle, monolymphocytic meningitis and dilated and congested blood vessels [4,11,16,17,20,21,[35][36][37][38][39]42]. We observed that the kidneys of the monkeys presented areas of necrosis, marked tubulonefrosis and ballooning degeneration with hyaline material, interstitial hemorrhage with increased Bowman space.…”
Section: Discussionsupporting
confidence: 91%
“…Infected persons can excrete the virus even in the absence of visible lesions [12]. Due to the severity of the disease, control and prevention measures should be instituted along with the Ecological Parks and breeding, such as the awareness of visitors not to feed the animals during the visitation, orientation of handlers on the need to wear appropriate clothing, gloves and masks, during treatment and feeding of animals, training of good management practices and hygiene in the enclosures, besides the adoption of procedures of quarantine to the new animals [14,16,36,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiviral drugs are classified as virucidals, immunomodulators and antiviral chemotherapeutic agents. Treatment of HSV infections is currently based on the use of several selective and effective drugs such as acyclovir, penciclovir, famciclovir, cidofovir, valacyclovir, trifluridine and vidarabine, which act as inhibitors of DNA polymerase [14,15]. Nevertheless, the intensive use of these drugs in the therapy has led to undesirable effects such as drug‐resistant strains [16].…”
Section: Introductionmentioning
confidence: 99%
“…The HSV-1 virus can be carried by human saliva in NHP food waste, and this can be fatal. 8 , 9 , 10 , 15 , 39 , 52 - 55 Pathogenicity in NWP HSV-1 is similar to the primary manifestations in humans, characterised by ulcerative vesicular lesions, oral, periocular, nasal, conjunctivitis, apathy, anorexia and ataxia, but it can be fatal in these animals. NWP are more susceptible to HHV-1 infections and diseases, the course of the disease is severe, leading to death in most cases.…”
Section: Discussionmentioning
confidence: 99%